-.05(2t-3)=0.5(9-4t)

Simple and best practice solution for -.05(2t-3)=0.5(9-4t) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -.05(2t-3)=0.5(9-4t) equation:


Simplifying
-0.05(2t + -3) = 0.5(9 + -4t)

Reorder the terms:
-0.05(-3 + 2t) = 0.5(9 + -4t)
(-3 * -0.05 + 2t * -0.05) = 0.5(9 + -4t)
(0.15 + -0.1t) = 0.5(9 + -4t)
0.15 + -0.1t = (9 * 0.5 + -4t * 0.5)
0.15 + -0.1t = (4.5 + -2t)

Solving
0.15 + -0.1t = 4.5 + -2t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '2t' to each side of the equation.
0.15 + -0.1t + 2t = 4.5 + -2t + 2t

Combine like terms: -0.1t + 2t = 1.9t
0.15 + 1.9t = 4.5 + -2t + 2t

Combine like terms: -2t + 2t = 0
0.15 + 1.9t = 4.5 + 0
0.15 + 1.9t = 4.5

Add '-0.15' to each side of the equation.
0.15 + -0.15 + 1.9t = 4.5 + -0.15

Combine like terms: 0.15 + -0.15 = 0.00
0.00 + 1.9t = 4.5 + -0.15
1.9t = 4.5 + -0.15

Combine like terms: 4.5 + -0.15 = 4.35
1.9t = 4.35

Divide each side by '1.9'.
t = 2.289473684

Simplifying
t = 2.289473684

See similar equations:

| 6y+67y=123 | | 56-(2c+4)=4(c-6)+c | | -4-6x=28 | | 6a-18=2a+26 | | 34=-8y+6(y+3) | | x-230-70-40=-44 | | D^8d+7= | | -.05(4a-1)=0.5(3-3a) | | 28=-12-4x | | -2m+13=sm-3 | | 6+2y=8y | | (14a+6)-(12a+5)= | | .25x+.75y=16 | | 3(m+3)=20 | | 3x+42-5x=1-8x+5 | | 2x-10=x+38 | | 144-48x+x^2=0 | | 51=-7x-26 | | 5x+8=9x-10 | | 5v*32=3v | | x^2+15x+49=17 | | 7(2x-1)=49 | | x+7+4-7-10=9 | | 11x+2.3=10x+3.1 | | 7(2x+1)=42 | | -x+4=-x+6 | | 2.3-7.9=10w-7.4-9w | | f(xy)=98x-y | | x^2+14x+49=17 | | (-2h)=(-1.46) | | y-10.5=-15 | | 2(3x+3)=2(x+1) |

Equations solver categories